Efficacy and Safety of a 3‐Weekly TS‐1 Adjuvant Regimen in Advanced Gastric Cancer: A Pilot Study - Jihong Bae; Joo‐Hwan Park; Young Saing Kim; Hee Kyung Ahn; Eun Kyung Cho; Dong Bok Shin; Ji‐Hyeon Park; Jun‐Young Yang; Woon Kee Lee; Sun Jin Sym (Cancer Medicine)
ABSTRACT Background TS‐1 at 80 mg/m2/day for 4 weeks followed by a 2‐week rest is standard adjuvant therapy for stage II/III Advanced Gastric Cancer (AGC). TS‐1 for 1 year (8 courses) is highly recommended. We investigated the efficacy and safety of an adjuvant 3‐weekly TS‐1 regimen for AGC. Methods We analyzed 93 patients with stage II/III AGC who started 3‐weekly adjuvant TS‐1 therapy between Feb 2017 and May 2022 post‐gastrectomy with D2 lymphadenectomy. The 3‐weekly regimen was TS‐1 at 80 mg/m2/day for 2 weeks, followed by a 1‐week rest for 1 year (16 courses). Results Among 93 patients, 12 (13%) had disease recurrence during follow‐up (median 24.6 months, range 4.2%–63.3%). Seven (9.5%) with stage II (n = 73) and five (25%) with stage III (n = 20) experienced recurrence. Kaplan–Meier analysis estimated that Recurrence‐Free Survival (RFS) rates at 1, 3, and 5 years were 92.0% (95% CI; 86.5%–97.9%), 84.7% (95% CI; 76.4%–93.9%), and 78.6% (95% CI; 65.8%–94.0%), respectively. Eighty patients (86%) completed the treatment; 25 (26.9%) needed dose reduction. Adverse events, mostly grade 1 or 2 diarrhea (28%) and nausea (20%), were manageable. Conclusion Our study revealed that the 3‐weekly TS‐1 regimen as adjuvant therapy exhibited good efficacy and manageable toxicity. This regimen as an adjuvant therapy for AGC should be evaluated in future studies.